2017
DOI: 10.1111/nph.14629
|View full text |Cite
|
Sign up to set email alerts
|

Recent origin and rapid speciation of Neotropical orchids in the world's richest plant biodiversity hotspot

Abstract: Summary The Andean mountains of South America are the most species‐rich biodiversity hotspot worldwide with c. 15% of the world's plant species, in only 1% of the world's land surface. Orchids are a key element of the Andean flora, and one of the most prominent components of the Neotropical epiphyte diversity, yet very little is known about their origin and diversification.We address this knowledge gap by inferring the biogeographical history and diversification dynamics of the two largest Neotropical orchid g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
174
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 105 publications
(160 reference statements)
11
174
6
2
Order By: Relevance
“…Factors affecting the diversification of lineages are often placed in two categories: (a) the abiotic factors (Barnosky, 2001) and (b) the biotic factors (Van Valen, 1973). Thanks to recent methodological developments, the relative contribution of abiotic and biotic factors to the variation of speciation and extinction rates has been assessed in various groups using fossil data (Ezard, Aze, Pearson, & Purvis, 2011;Lehtonen et al, 2017;Liow, Reitan, & Harnik, 2015;Roalson & Roberts, 2016;Silvestro, Antonelli, Salamin, & Quental, 2015) or phylogenetic data (Condamine, Rolland, Höhna, Sperling, & Sanmartín, 2018;Condamine, Sperling, Wahlberg, Rasplus, & Kergoat, 2012;Lagomarsino, Condamine, Antonelli, Mulch, & Davis, 2016;Pérez-Escobar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the diversification of lineages are often placed in two categories: (a) the abiotic factors (Barnosky, 2001) and (b) the biotic factors (Van Valen, 1973). Thanks to recent methodological developments, the relative contribution of abiotic and biotic factors to the variation of speciation and extinction rates has been assessed in various groups using fossil data (Ezard, Aze, Pearson, & Purvis, 2011;Lehtonen et al, 2017;Liow, Reitan, & Harnik, 2015;Roalson & Roberts, 2016;Silvestro, Antonelli, Salamin, & Quental, 2015) or phylogenetic data (Condamine, Rolland, Höhna, Sperling, & Sanmartín, 2018;Condamine, Sperling, Wahlberg, Rasplus, & Kergoat, 2012;Lagomarsino, Condamine, Antonelli, Mulch, & Davis, 2016;Pérez-Escobar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Andean orchids (Pérez‐Escobar et al. ), asynchronous migrations from adjacent regions followed by rapid diversification have led to extremely high species diversity in montane areas. This contradicts the museum hypothesis, whereby species accumulate at a constant rate over time with little extinction.…”
mentioning
confidence: 99%
“…Diversification patterns of corals in the CT resemble the diversification dynamics of other eukaryotic lineages that are highly diverse in biodiversity hotspots. For example, in Andean orchids (Pérez-Escobar et al 2017b), asynchronous migrations from adjacent regions followed by rapid diversification have led to extremely high species diversity in montane areas. This contradicts the museum hypothesis, whereby species accumulate at a constant rate over time with little extinction.…”
mentioning
confidence: 99%
“…; Gentry ; Pérez‐Escobar et al. ). It has been argued that the great variation in angiosperm flowers is largely influenced by pollinator‐mediated selection (Sauquet et al.…”
mentioning
confidence: 99%
“…), a force that has also been linked with diversification of large groups within the flowering plants, such as orchids (Pérez‐Escobar et al. ). Micro‐evolutionary studies aimed at understanding mechanisms underpinning changes in observed phenotypes have clearly demonstrated that pollinator shifts are strongly correlated with changes in floral traits (e.g., Aquilegia ; Whittall and Hodges ).…”
mentioning
confidence: 99%